Lithuanian National Cultural Periodical Publishing in 1997–2018: Processes of Change and Adaptation - Urbanavičiūtė-Globienė, Asta (Knygotyra, 2025)
Cultural periodicals are an important part of a nation’s cultural identity, and their mission is cultural reflection. This article analyzes the main changes in publishing which took place in the field of Lithuanian cultural periodicals during the period from 1997 to 2018. The study focuses on Lithuanian national cultural periodical publications, aiming to highlight specific aspects of their publishing along with their place within a broader field of periodical publishing. The goal of this article is to examine the distinctive features of Lithuanian national cultural periodical publishing in the context of the general periodical publishing landscape from 1997 to 2018. The publishing characteristics of cultural periodicals issued during this period are analyzed through key publishing aspects: the article focuses on the typology of the publications, their periodicity, circulation trends, and distribution strategies. Based on these criteria, the study explores how cultural publications changed both quantitatively and qualitatively, and what trends emerged during the analyzed period. Despite facing numerous challenges during this time – such as decreasing funding, declining circulation, and audience fragmentation – cultural periodicals remained a vital source for shaping cultural identity and fostering intellectual discourse. These publications sought ways to maintain high-quality content and reinforced their mission to inform, educate, and reflect upon cultural processes.